Examining Organic and Elemental Carbon Presence in Beauty Salon Service Rooms - Patrycja Rogula-Kopiec; Wioletta Rogula-Kozłowska; Jan Stefan Bihałowicz; Artur Badyda; Kamila Widziewicz-Rzońca; Barbara Mathews; Grzegorz Majewski; Piotr Oskar Czechowski (Aerosol and Air Quality Research)
Abstract Purpose The study was designed to investigate the concentrations and potential sources of elemental carbon (EC) and organic carbon (OC) associated with particulate matter of diameter < 2.5 µm (PM2.5) in the indoor air of nine beauty salons. The carbon matrix of these particles can carry toxic compounds, potentially adversely affecting the health of salon employees. Methods  Filtres with PM2.5 were analyzed for OC and EC content with Model 4L Sunset Laboratory thermal-optical OC/EC analyser. Samples were taken from hair salons (H1–H3), nail studios (N1-N3) and cosmetic studios (C1–C3) in Silesia to gain insight into emission conditions at each salon using Gilian 12 Air Sampling Pumps with PM2.5 cyclones. Results Median PM2.5 concentrations ranged from 8.82 to 55.66 µg/m3, OC from 3.33 to 5.66 µg/m3 for H1 and C1, respectively, while median EC ranged from 0.003 to 0.32 µg/m3 for H1 and N2, respectively. The ratios of PM, OC, and EC concentrations indoors and outdoors were significantly higher than one, except for EC in H1. The median OC content of total carbon varied from 93.09% for H2 to 99.91% for H1, while the OC composition differed significantly from the background, except for sites N3 and C2. Conclusions The differences can be attributed to the use of specific cosmetics salons, ventilation systems, window types and volume. The predominance of organic carbon underscore the need to prioritize air in beauty salons and require further research on pollutant dynamics, direct mitigation of human health impacts including improved ventilation and staff training to reduce emissions. Graphical abstract